2022
DOI: 10.3389/fpubh.2022.907522
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Social Media Disorder Scale using network analysis in a large representative sample of Czech adolescents

Abstract: BackgroundThe importance of studying the excessive use of social media in adolescents is increasing and so is the need for in-depth evaluations of the psychometric properties of the measurement tools. This study investigated the properties of the Social Media Disorder Scale (SMDS) in a large representative sample of Czech adolescents.MethodsWe analyzed the representative sample of 13,377 Czech adolescents (50.9% boys), 11–16 years old, who participated in the Health Behavior in School-aged Children (HBSC) surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…To meet the diagnostic criteria for IGD or SMD, a substantial amount of screen time is likely required (Pontes et al, 2022), and the DSM-5 (American Psychiatric Association, 2013) states that individuals with IGD typically devote 8-10 h/day or at least 30 h/ week to gaming. Studies that have examined the association between screen time and addictive use have found support for this association for both gaming (e.g., Männikkö et al, 2015;Bouna-Pyrrou et al, 2018;Jeong et al, 2021;Jin et al, 2022;Jo et al, 2022) and social media (e.g., Bouna-Pyrrou et al, 2018;Guo et al, 2021;Šablatúrová et al, 2022;Tomczyk and Lizde, 2023). However, most previous studies did not measure addictive digital media use based on the nine criteria presented for IGD in the DSM-5 (American Psychiatric Association, 2013).…”
Section: Screen Time and Symptoms Of Igd/smdmentioning
confidence: 99%
“…To meet the diagnostic criteria for IGD or SMD, a substantial amount of screen time is likely required (Pontes et al, 2022), and the DSM-5 (American Psychiatric Association, 2013) states that individuals with IGD typically devote 8-10 h/day or at least 30 h/ week to gaming. Studies that have examined the association between screen time and addictive use have found support for this association for both gaming (e.g., Männikkö et al, 2015;Bouna-Pyrrou et al, 2018;Jeong et al, 2021;Jin et al, 2022;Jo et al, 2022) and social media (e.g., Bouna-Pyrrou et al, 2018;Guo et al, 2021;Šablatúrová et al, 2022;Tomczyk and Lizde, 2023). However, most previous studies did not measure addictive digital media use based on the nine criteria presented for IGD in the DSM-5 (American Psychiatric Association, 2013).…”
Section: Screen Time and Symptoms Of Igd/smdmentioning
confidence: 99%